Isolated and combined organic acids in diets of broiler chickens challenged with Eimeria acervulina - Cruz-Polycarpo, V. C. [UNESP]; Freschi, J. B. [UNESP]; Polycarpo, G. V. [UNESP]; Araujo, R. G.A.C. [UNESP]; Barbieri, A. [UNESP]; Sousa, R. L.M. (FapUNIFESP (SciELO), 2020)
This study aimed to evaluate the effect of isolated or combined citric and benzoic acids added to the diets of broiler chickens on performance, allometry of the digestive system organs, intestinal pH and quantity of microorganisms in the jejunum. A total of 840 male Cobb broiler chicks were utilized, distributed in a complete random design in 2 x 2 factorial scheme, supplemented or not with citric acid, and sodium benzoate, with seven replications. At 14 days old, 1mL of a solution containing 1 x 105 sporulated oocysts of Eimeria acervulina per bird was inoculated orally. There was no effect of the acids on the broiler's performance in the 1 to 21-day period. In the total period (1 to 42 days), the broilers fed with a blend of citric and benzoic acid presented greater feed intake, without increment in weight gain. The data of allometry of the digestive system organs and the jejunal pH values were not influenced by the treatments. The citric acid increased the bacterial quantity of gram-positive coccus and total anaerobes in the jejunum. Under the conditions of the present study, we conclude that the citric and benzoic acids, isolated or combined, do not benefit the nutrition of broilers challenged with E. acervulina.
Keywords: Acidifying; Additive; Gastrointestinal tract; Microbiota; Performance; Poultry